Ankle arthritis: which to choose – arthrodesis or arthroplasty - Mohd Yazid Bajuri,; Abdullah A, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
The best treatment option in ankle arthritis have always been debated. It is either ankle arthroplasty or arthrodesis. The incidence of ankle arthritishas increased over the recent decades due to the increasing life span of the population and incidence of injuries sustained during sporting events. Although arthrodesis is still largely regarded as the gold standard for it is a safe procedure but in long term, several studies have reported complications such as arthritis in adjacent joints, hip dysfunction and knee problems. Currently results have shown that ankle arthroplasty offers a better long term results than arthrodesis especially in view of patient’s satisfaction and its good functional outcome. This review article aims to analyse both options and their respective outcomes.